2017
DOI: 10.1093/europace/eux095
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in cardiovascular disease in Europe with focus on arrhythmias: current status, opportunities, roadblocks, and the role of multiple stakeholders

Abstract: The European Heart Rhythm Association (EHRA) held an Innovation Forum in February 2016, to consider issues around innovation. The objective of the forum was to extend the innovation debate outside of the narrow world of arrhythmia specialists and cardiology in general, and seek input from all stakeholders including regulators, strategists, technologists, industry, academia, health providers, medical societies, payers, and patients. Innovation is indispensable for a continuing improvement in health care, prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…21.2% (n=7) of studies identified 'HTA' as a barrier to medical device diffusion [5,6,9,42,44,45,48].…”
Section: ) Health Technology Assessment (Hta)mentioning
confidence: 99%
See 3 more Smart Citations
“…21.2% (n=7) of studies identified 'HTA' as a barrier to medical device diffusion [5,6,9,42,44,45,48].…”
Section: ) Health Technology Assessment (Hta)mentioning
confidence: 99%
“…The subtheme of 'process' (n=3, 42.3%) [42,44,45] related to limitations in HTA processes that delay access to a technology due to several issues including the complex submission requirements and overall lack of transparency/clarity for timelines and evaluation processes. Additionally, 'decision-maker characteristics' (n=3, 42.3%) [5,9,44] can be associated with the HTA process, as biases, a lack of appropriate expertise, or the general backgrounds and training of members in the assessing committees can influence the final decision.…”
Section: ) Health Technology Assessment (Hta)mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, models linking cellular electrophysiology, myocardial tissue mechanics, and system haemodynamics have become promising platforms for virtual-patient simulations and for in silico evaluation of novel diagnostic and therapeutic strategies 188 . These biophysically detailed models of the heart are having an increasingly important role in the road to personalized medicine in cardiology clinics 189,190 . In this time of growing regulatory and administrative burdens that restrict the ability to develop new drugs, medical devices and diagnostic technologies, simulations of virtual patients and therapy provide the means for the pharmaceutical and biomedical device industries to reduce the developmental costs of innovation and the time to market 189 .…”
Section: The Future Of Computational Modelsmentioning
confidence: 99%